Tute 3 PDF
Tute 3 PDF
Tute 3 PDF
1. Find the partial differential equations by eliminating the arbitrary constants from the following
equations:
√
(a) z = ax + y x2 − a2 + b (b) z = axey + 12 a2 e2y + b
2 2
x y
(c) 2z = a2 + b2 (d) log(az − 1) = x + ay + b
2. (a) Find the partial differential equation of all planes which are at a constant distance from
origin.
(b) Find the partial differential equation of the set of all right circular cones whose axes coincide
with z-axis.
(c) Find the partial differential equation of all cones which have their vertex at the origin.
(d) Find the partial differential equation of the family of planes, the sum of whose x,y,z intercepts is
equal to unity.
3. Find the partial differential equation by eliminating arbitrary functions from the following
relations
(a) z = f (xy) + g( xy ) (b) f (x + y + z, x2 + y 2 + z 2 ) = 0 (c) lx + my + nz = φ(x2 + y 2 + z 2 )
y−b
(d) f ( x−a
z−c , z−c ) = 0 (e) f (x + y + z) = xyz
(a) cos(x + y)p + sin(x + y)q = z (b) py + qx = xyz 2 (x2 − y 2 ) (c) (x2 + 2y 2 )p − xyq = xz,
(d) z(xy + z 2 )(px − qy) = x4 (e) (x2 − y 2 − yz)p + (x2 − y 2 − zx)q = z(x − y)
1
(9) Solve the following partial differential equations
Answers
∂z ∂z ∂z ∂z ∂z ∂z 2 ∂z ∂z ∂z
1. (a) ∂x ∂y = a ∂y + xy (b) ∂y = x ∂x + ( ∂x ) (c) 2z = px + qy (d) (1 + ∂y ) ∂x = z ∂y
∂z ∂z pq
p
2. (a) z = px + qy + a p2 + q 2 + 1, (b) y ∂x = x ∂y , (c) px + qy = z (d) px + qy − z = p+q−pq
∂z
3. (a) x2 r − y 2 t + xp − yq (b) p(y + z) − (x + z)q = x − y (c) (nx − mz) ∂x + (lz − nx) ∂z
∂y = mx − ly
5. (a) f ( x−y 2
y−z , (x − y) (x + y + z)) = 0 (b) f (xy + yz + zx, x−y
y−z ) = 0 (c) f (y 2 + z 2 , x
−1 ( y ) )=0
etan z
a−1
1
(d) f (x+y, 2 log z 2 + (x + y)2 )=0 (e) φ( xy , √ x
) =0
x2 +y 2 +z 2
2
a
6. (a) z = ax − + ψ(a)
1+a y (b) z − ax + ( a2 + 3a + 2)y − ψ(a) = 0
√
(c) z − ax − a2 (n + n2 − 4)y − ψ(a) = 0 (d) z − ax − log(ay) − ψ(a) = 0
p
(e) z = ax + y (m2 − a2 ) + φ(a).
p p
7. (a) z − ax − ψ(a)y − 4 1 + a2 + (ψ(a))2 = 0 (b) z − ax − ψ(a)y − αa2 + β(ψ(a))2 + 1 = 0
1
m−n m−n−l
(1−am ) n
(c) m−n−l z
m−n = a4 (2x + sin2x) + 4(2y − sin2y) + ψ(a)
√ √
1−a2
a 2 z
p
(d) x y = ψ(a)e (e) z − ax − ψ(a)y − 2 (a)ψ(a) = 0